MENINGKATKAN KEMAMPUAN GURU MENGORKESTRASI PEMBELAJARAN MeNaRIK MELALUI KEGIATAN FIG - Siregar, Salamat (Jurnal Manajemen Pendidikan, 2022)
The massive expansion of Covid-19 to all aspects of life has forced mankind to form a new order that we commonly call the new normal. One of the sectors of life that suffers the most is the education sector, namely the occurrence of learning loss, which is a condition of loss of effective learning opportunities for students and a decrease in mastery of competencies. Ideas that are worthy of being used as alternative solutions to overcome learning problems during the COVID-19 pandemic are through school policies that favor students, that is "MeNaRIK" learning which is an acronym for Fun, Meaningful, Interactive, Innovative, and Collaborative is an alternative solution to help solve current educational problems. The purpose of this research is to improve the ability of teachers in orchestrating MeNaRIK learning through the activities of the Teacher Scientific Forum (FIG). The research method used is school action research (SAR) with 15 people as the subject of the research being the teachers of SMA Negeri 1 Angkola Barat. The instrument used to collect research data was an observation sheet to observe the teacher's ability to make the best lesson plans and to orchestrate the MeNaRIK learning. The results showed that the teacher's ability in preparing the MeNaRIK learning plan was 45.22 in cycle 1, 66.33 in cycle 2, and 78.11 in cycle 3. Meanwhile, the teacher's ability to orchestrate MeNaRIK learning was 54.25 in cycle 1, 71, 50 in the 2nd cycle, and 77.58 in the 3rd cycle. The conclusion is that the implementation of FIG as a collaborative space for teachers in carrying out learning improvement exercises has succeeded in increasing the average ability of teachers in preparing lesson plans and conducting orchestration of MeNaRIK learning, even though the set targets have not been achieved.